Decrease in sick leave among patients with rheumatoid arthritis in the first 12 months after start of treatment with tumour necrosis factor antagonists: a population-based controlled cohort study. Issue 12 (6th August 2010) - Olofsson, Tor; Englund, Martin; Saxne, Tore; Jöud, Anna; Jacobsson, Lennart T H; Geborek, Pierre; Allaire, Saralynn; Petersson, Ingemar F
Abstract : Objective: To investigate the effect of tumour necrosis factor (TNF) antagonist treatment of patients with rheumatoid arthritis (RA) on sick leave (SL) and disability pension (DP) in a population-based setting in southern Sweden. Methods: All patients with RA in the South Swedish Arthritis Treatment Group register living in the county of Skåne (population 1.2 million), who started their first treatment with a TNF antagonist between January 2004 and December 2007 and were 18–58 years at treatment start (n=365), were identified. For each patient with RA, four matched reference subjects from the general population were randomly selected. Data were linked to the Swedish Social Insurance Agency register and the point prevalence of SL and DP as well as days of SL and DP per month were calculated from 360 days before until 360 days after treatment start. Results: At treatment start 38.6% of the patients with RA were registered for SL. During the first 6 months this share dropped to 28.5% (decrease by 26.2%, p<0.001). This level remained stable throughout the first treatment year. Comparing patients with RA to the reference group the relative risk of being on SL was 6.6 (95% CI 5.2 to 8.5) at initiation of anti-TNF treatment and 5.2 (95% CI 4.0 to 6.8) 1 year after that. The corresponding figures for DP were 3.4 (95% CI 2.7 to 4.2) and 3.2 (95% CI 2.7 to 3.9). Conclusions: There was a marked decline in SL during the first 6 months of TNF antagonist treatment in patients with RA in southern Sweden, maintained throughout the first year, which was not offset by a corresponding increase in DP.